FRAKSI BESI DAN PENGARUHNYA TERHADAP KELARUTAN POSFOR DI LAHAN RAWA (Iron Fraction And Its Effect On Posforning Sustainability In Rawa Land): Fahmi, A. 1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTAbout 20 million Ha of tidal swampare found in Indonesia,6.7 million ha of them are acid sulphatesoils which associated with peatland.Most of soil in tidal swamp are rich in iron, it potentialy toxicto the plant. We critically examine the presence of peat matter as surface layer to iron fraction andthe role of ferrous to phosphorus (P) solubility in soil.Iron fractions analyzed in acid sulphate soil,peaty acid sulphate soil, shallow peatland, shallow peatland which all of peat layers were removedand shallow peatland which partially of peat layers were removed. Most of iron fraction in tidalswampland which covered by peat layer is organic-Fe form, the presence of peat layer on surfacelayer caused no correlation between Fe and P in soil.Key words : Acid sulphate soil, Iron, Peatland, Phosphorus andTidal swampland